2018
DOI: 10.1055/s-0038-1673655
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Intended Mode of Delivery and Maternal Morbidity in Twin Pregnancies

Abstract: Objective To compare maternal morbidity between women undergoing delivery of twins who intend to labor with those women who do not intend to labor. Study Design This was a retrospective cohort study of women undergoing delivery of twins in a single maternal–fetal medicine practice between January 2005 and February 2018. We identified women with a twin delivery at gestational age ≥24 weeks and determined if they intended or did not intend to labor. Maternal outcomes were compared between the groups.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…A total of 788 twin pregnancies between 2005 and 2018 were included in a recent study that was conducted by Zafman et al, and no differences were reported between delivery types and maternal mor-tality and morbidity. [9] There were rare serious maternal complications in the same study such as thrombosis, hysterectomy, bowel or bladder injury, and admission to ICU, and there were no differences between the groups. [9] Also, there were no significant differences between 3rd and 4th-degree laceration, endometritis, wound complications, and blood transfusion rates.…”
Section: Discussionmentioning
confidence: 76%
See 4 more Smart Citations
“…A total of 788 twin pregnancies between 2005 and 2018 were included in a recent study that was conducted by Zafman et al, and no differences were reported between delivery types and maternal mor-tality and morbidity. [9] There were rare serious maternal complications in the same study such as thrombosis, hysterectomy, bowel or bladder injury, and admission to ICU, and there were no differences between the groups. [9] Also, there were no significant differences between 3rd and 4th-degree laceration, endometritis, wound complications, and blood transfusion rates.…”
Section: Discussionmentioning
confidence: 76%
“…[9] There were rare serious maternal complications in the same study such as thrombosis, hysterectomy, bowel or bladder injury, and admission to ICU, and there were no differences between the groups. [9] Also, there were no significant differences between 3rd and 4th-degree laceration, endometritis, wound complications, and blood transfusion rates. [9] In our study, the complications such as thrombosis, endometritis, hysterectomy, bowel or bladder injury, and blood transfusions were rare in the groups, and we found no differences between the groups in this respect.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations